2014
DOI: 10.1002/ajpa.22457
|View full text |Cite
|
Sign up to set email alerts
|

Diet of upper paleolithic modern humans: Evidence from microwear texture analysis

Abstract: This article presents the results of the occlusal molar microwear texture analysis of 32 adult Upper Paleolithic modern humans from a total of 21 European sites dating to marine isotope stages 3 and 2. The occlusal molar microwear textures of these specimens were analyzed with the aim of examining the effects of the climatic, as well as the cultural, changes on the diets of the Upper Paleolithic modern humans. The results of this analysis do not reveal any environmentally driven dietary shifts for the Upper Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 61 publications
0
20
0
1
Order By: Relevance
“…Explanations for these instances of high forager anisotropy tend to connect diet to the ecogeographic region in which groups lived; in places where tough/fibrous foods were readily available sources of nutrition, they were consumed. El Zaatari and colleagues noted this relationship in recent archeological groups (El Zaatari, , ), anatomically modern humans of the Upper Paleolithic (El Zaatari & Hublin, ), and Neandertals (e.g., El Zaatari, Grine, Ungar, & Hublin, ). Since then, other researchers have drawn similar conclusions, particularly regarding Neandertals (e.g., Karriger et al, ; Williams et al, ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Explanations for these instances of high forager anisotropy tend to connect diet to the ecogeographic region in which groups lived; in places where tough/fibrous foods were readily available sources of nutrition, they were consumed. El Zaatari and colleagues noted this relationship in recent archeological groups (El Zaatari, , ), anatomically modern humans of the Upper Paleolithic (El Zaatari & Hublin, ), and Neandertals (e.g., El Zaatari, Grine, Ungar, & Hublin, ). Since then, other researchers have drawn similar conclusions, particularly regarding Neandertals (e.g., Karriger et al, ; Williams et al, ).…”
Section: Discussionmentioning
confidence: 93%
“…A final concern regarding ancient human microwear is that DMTA was developed for interspecific comparisons. Nonetheless, microwear analysis has been employed in a number of intraspecific studies as well (Casserly, Van Sessen, & Schmidt, ; Chiu, Schmidt, Mahoney, & McKinley, ; El Zaatari, , ; El Zaatari & Hublin, ; El Zaatari & Teaford, ; Estalrrich, El Zaatari, & Rosas, ; Estalrrich & Rosas, ; Karriger et al, ; Krueger, ; Krueger & Ungar, ; Larsen et al, ; Ma & Teaford, ; Mahoney et al, ; Organ, Teaford, & Larsen, ; Schmidt et al, ; Schmidt & Remy, ; Teaford & Robinson, ; Williams et al, ). An intraspecific study of humans is a challenge because human dietary strategies tend to overlap, even among people with disparate subsistence strategies.…”
Section: Caveatsmentioning
confidence: 99%
“…Moreover, they should also focus on potentially different patterns based on the stone‐tool technology used and other functional aspects. For example, El Zaatari and Hublin () found that changes in microwear texture signals of modern human teeth can be associated with major technological complexes of the Upper Paleolithic. More specifically, the analysis of the microwear texture showed significant differences between individuals from Aurignacian and Gravettian contexts relative to those of Magdalenian culture, with the latter characterized by a more abrasive diet (El Zaatari & Hublin, ).…”
Section: Discussionmentioning
confidence: 99%
“…A few bioarchaeological studies have employed microwear texture analysis (El Zaatari, ; El Zaatari & Hublin, ; Krueger, ; Schmidt et al, ). El Zaatari focused on recent and Upper Palaeolithic foragers and found that groups consuming more plant matter and less meat evince higher molar microwear texture complexity (El Zaatari, ; El Zaatari & Hublin, ). Schmidt et al () likewise reported that pastoralists have lower molar microwear texture complexity, anisotropy, and textural fill volume (a measure of feature size) than do agriculturalists.…”
Section: Introductionmentioning
confidence: 99%